IMPROVING STUDENTS’ READING COMPREHENSION BY USING NUMBERED HEADS TOGETHER FOR EIGHT B GRADE AT MTS AL-MA’ARIF SINGOSARI MALANG - nasrul miftahur riza (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Reading skill is really important and needed by students in developing their ability in comprehending English text. Besides, many students do not like and interest to reading activity in the class because reading is a boring activity for students. Therefore, This research used Numbered Heads Together (NHT) Technique that is appropriate to be used in the class in order that students were not bored anymore because NHT Technique can help students to enjoy and follow English subject well in the class. Additionally, NHT Technique is a group system in which students are divided into some groups and given number; the members had the same numbers group. It is able to make students discuss and solve problem together confidently. This research aimed to know the implementation of NHT as a teaching and learning technique to improve student’s reading comprehension at VIII B class in MTs Al Ma’arif Singosari Malang. The researcher used classroom action research to conduct this study. The subject of this research was the students of MTs Al Ma’arif Singosari Malang. Then, the sample of this research was 35 students of VIII B class. the researcher used some instruments; those are: did preliminary test, applying NHT Technique, and final-test. This study used Classroom Action Research (CAR) as a method and average of criteria of success in this study was 75 above. Moreover, The result of this research showed that average score of preliminary test was 55.7 from 35 students. After the researcher conducted the research using NHT Technique, the students’ average score was 76.4 from 35 students. It indicated that NHT Technique had successfully improved students’ scores and reading comprehension in one cycle. Consequently, the researcher hopes that the future researcher can use NHT Technique to be implemented in other skill of language learning, such as writing, speaking and listening. Besides the researcher hopes the teacher is able to be more creative in teaching and learning English.Key Word: Improving, Reading Comprehension, Numbered Heads Together